The Existence of Human Rights in A Shift in The Concept of The State of Law - Siswadi, Imran; Supriadi, Supriadi (UNISKA LAW REVIEW, 2023)
Human rights have become an essential element in international politics, especially after the end of the Cold War in the 1990s. The problem in this research is "How the existence of human rights in the shifting concept of the state of law and human rights enforcement in Indonesia." The study of normative law tries to analyze, investigate, and explain the basics and political position backgrounds of human right in the history of the human rights development. The research results show that there are at least three main themes often highlighted by human rights violations in Indonesia. The fact that government actions that violate the principles of constitutionalism, especially violating human rights, can always be formally justified constitutionally because they are given legal clothing in the form of laws or other laws and regulations has caused a shift in principles and concepts from a states of law that happens a lot in Indonesia, namely, the change of the states of laws into a state of laws that lays down laws created by the government as a measure of truth. The government generally uses accusations of undermining government authority against those who are considered contrary to government policy.